2023
DOI: 10.3390/systems11060284
|View full text |Cite
|
Sign up to set email alerts
|

Leading Role of Big Data Analytic Capability in Innovation Performance: Role of Organizational Readiness and Digital Orientation

Abstract: The advancement of technology offers various opportunities for business organizations to achieve sustainable growth. Through emerging technologies, business organizations are able to collect and analyze essential information vital for the acceleration of innovation. Therefore, this study investigated how big data contribute to the innovation activities of manufacturing entrepreneurs in terms of big data analytic capability (BDAC). The aim of this study was to relate BDAC to organizational readiness and innovat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…This study suggested positive and direct relationships among the main variables. First, its finding confirms the positive direct relationship between BDACs and IP, and it is consistent with previous studies [4,11,35,44,45,72,74]. Second, regarding the hypothesis that stated that there is a positive relationship between SIC and IP, the finding of this study is in line with previous research [6,51,63,64].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study suggested positive and direct relationships among the main variables. First, its finding confirms the positive direct relationship between BDACs and IP, and it is consistent with previous studies [4,11,35,44,45,72,74]. Second, regarding the hypothesis that stated that there is a positive relationship between SIC and IP, the finding of this study is in line with previous research [6,51,63,64].…”
Section: Discussionsupporting
confidence: 92%
“…The term BDACs refers to a firm's ability to leverage big data to gain strategic and operational insight [8,[42][43][44]. It also pertains to the firm's ability to assemble, integrate, and deploy its big data-specific resources [9].…”
Section: Big Data Analytics Capabilities (Bdacs)mentioning
confidence: 99%
See 2 more Smart Citations
“…Jun et al (2022) reveal a significant and positive relationship between digital platform capability, improvisational capability, organizational readiness, and innovation performance. Binsaeed et al (2023) find that Big Data and Analytics Capabilities (BDAC) are vital in developing organizational readiness and intellectual property. Jones et al (2005) find that change readiness is a mediated connection between system utilization and reshaping capacities.…”
Section: Digital Capabilities and Organizational Readinessmentioning
confidence: 99%